SOCIO-LEGAL BASIS FOR THE PROTECTION OF WOMEN AND CHILDREN IN CASES OF DOMESTIC VIOLENCE MODEL OF SOCIO-PSYCHOLOGICAL ASSISTANCE IN THE FAMILY - Shodieva Zebiniso Nurmamadovna (American Journals Publishing, 2022)
In this article, the author tried to analyze the social legal framework for the protection of women and children in case of domestic violence. Particular attention in society is paid to issues of harassment and violence against women in relation to the protection of women from violence, crime.
Keywords: women, violence, intolerance, harassment, law, material damage, domestic violence, protection, agreement, discrimination